OPERATION PHAKISA: REFLECTIONS UPON AN AMBITIOUS MARITIME-LED GOVERNMENT INITIATIVE - Vreÿ, Francois (Scientia Militaria - South African Journal of Military Studies, 2020)
Operation Phakisa enjoys ‘presidential’ status as a project launched by and housed within the Presidency of the Republic of South Africa during the Zuma administration. Phakisa is a most ambitious project, which includes a prominent maritime component. The maritime focus functions as one catalyst for positioning South Africa as an international maritime player by 2030 and in the process speeding up national development through delivery of public goods, economic growth and jobs. Aiming to be an international maritime player supposes that foreign policy elements also feature in the project considerations. Launched in 2014, Phakisa’s oceans leg now offers scope for scrutiny as mixed messages about its progress and failures routinely appear. The gist of the discussion is forward-looking, with Operation Phakisa’s progress, failures and prospects to achieve government’s 2030 maritime aims and objectives constituting the focus of the discussion. The study on which this article is based, found that Operation Phakisa’s oceans leg depicts an impressive government ambition to exploit a new frontier, one reflecting progress and failures with promises of rapid big results being the most visible failure.